2015
DOI: 10.1039/c4cy00883a
|View full text |Cite
|
Sign up to set email alerts
|

Three consecutive steps over the chirally modified Pt surface: asymmetric catalytic cascade reaction of 2-nitrophenylpyruvates

Abstract: The influence of the reaction conditions on the asymmetric heterogeneous catalytic reaction of 2-nitrophenylpyruvates over Pt modified with cinchonidine showed that all three steps of the cascade occur on the metal surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Recently, optically enriched 3hydroxy-3,4-dihydroquinolin-2(1H)-one derivatives have been successfully prepared by a newly developed heterogeneous catalytic asymmetric cascade reaction over supported Pt catalysts in the presence of H2 and cinchona alkaloid chiral modifiers (Fig. 1) [2,3]. Cascade reactions, also known as domino reactions or tandem reactions, are chemical processes in which at least two consecutive steps occur, therefore, incorporate multiple bond-forming events carried out in one-pot manner.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, optically enriched 3hydroxy-3,4-dihydroquinolin-2(1H)-one derivatives have been successfully prepared by a newly developed heterogeneous catalytic asymmetric cascade reaction over supported Pt catalysts in the presence of H2 and cinchona alkaloid chiral modifiers (Fig. 1) [2,3]. Cascade reactions, also known as domino reactions or tandem reactions, are chemical processes in which at least two consecutive steps occur, therefore, incorporate multiple bond-forming events carried out in one-pot manner.…”
Section: Introductionmentioning
confidence: 99%
“…The starting materials of our cascade reaction are the 2'-nitrophenylpyruvates. The transformation of nitrophenylpyruvates follows two different pathways: one with formation of indole derivatives, another with formation of the desired quinoline derivatives [3]. The composition of the product mixture strongly depends on the reaction conditions as type and amount of catalyst and cinchona alkaloid chiral template, reaction temperature, H2 pressure, pH of the solvent, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Asymmetric hydrogenation of α-ketoester on cinchonidine (CD) modified Pt catalysts has been regarded as one of the milestones in heterogeneous asymmetric catalysis. New findings and applications can still be seen in recent years [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The intermediate 156 bearing both hydroxyl and amino groups desorbed from the Pt surface and was further transformed following readsorption after consumption of the pyruvates 154. 204 The highest ee values were obtained using CM2* as chiral modifier. Substituents on the phenyl ring of 154 had significant effects on both the yield and the ee by influencing the rate of the -NO 2 group reduction, and as a consequence the product distribution and by affecting the substrate-modifier interaction.…”
mentioning
confidence: 99%
“…Aromatic nitro group reduction was also one of the steps of a one-pot cascade reaction developed recently over Pt catalyst modified by cinchona alkaloids. 203,204 The hydrogenation of 2-nitrophenylpyruvates 154 over chirally modified Pt catalysts resulted in the formation of optically enriched 3-hydroxy-3,4-dihydroquinolin-2IJ1H)-ones 157 (Scheme 46), instead of the indole-2-carboxylates usually formed via Reissert indole synthesis if other reduction methods are applied. Although in this cascade reaction the first two reductive steps are also competitive, the high yields of the quinolone derivatives 157 showed that the enantioselective hydrogenation accelerated by the presence of the chiral modifier preceded the reduction of the nitro group.…”
mentioning
confidence: 99%